(untitled) (Al-Farooq Journal of Sciences, 2026)
This research examines legal standing as an essential condition for the admissibility of judicial actions. It explains its concept and legal nature and distinguishes it from legal interest, litigation capacity, and representation in legal proceedings. The study also addresses the different forms of standing, including ordinary and extraordinary substantive standing, procedural standing, exceptional standing, and standing related to the protection of public interests. The descriptive-analytical method was adopted by examining the provisions of the Libyan Code of Civil and Commercial Procedure and comparing them with selected Arab legal systems, particularly the Egyptian, Algerian, and Moroccan systems. The research concludes that an action must be brought by a person with legal standing against a defendant with proper standing. It also finds that procedural standing differs from substantive standing and that exceptional standing must be expressly established by law. Furthermore, lack of standing may constitute a procedural, substantive, or special plea, and standing is a matter of public order that courts must examine on their own initiative.